Legal Risk Mitigation Issues in the Procurement of Goods and Services from a Corporate Law Perspective (A Case Study at PT Perkebunan Nusantara IV Regional I) - Hady, Faisal; Siregar, Mahmul; Mulyadi, Mahmud (Mahadi: Indonesia Journal of Law, 2025)
The procurement of goods and services in the public sector is regulated by Presidential Regulation (Perpres) No. 12 of 2021, while procurement in state-owned enterprises (SOEs) is governed by the Ministry of SOEs Regulation No. PER-2/MBU/03/2023. PT Perkebunan Nusantara IV (PTPN IV), a palm oil plantation SOE subsidiary, utilizes the Integrated Procurement System (IPS) for its procurement processes. However, the clarification stage is still conducted through in-person meetings to verify original documents, posing risks of abuse of authority and regulatory violations. This practice does not fully reflect the implementation of Good Corporate Governance (GCG) within PTPN IV Regional I. This study is a normative juridical and descriptive-analytical research, using a statutory approach, library research, and field research through in-depth interviews. The findings indicate that risk mitigation in procurement is crucial to ensure smooth operations and prevent disruptions to quality, cost, and timing. Although PTPN IV complies with current regulations, the use of a Presidential Regulation is considered to lack sufficient legal authority, particularly in the context of decentralization. Thus, the establishment of a Goods and Services Law is necessary to provide a stronger legal foundation for public procurement. Furthermore, regular training for procurement staff on legal frameworks, contract management, legal risk mitigation, and dispute resolution is essential to minimize legal risks and ensure that procurement is conducted transparently, efficiently, and accountably in accordance with good governance principles.